Features injuries handball players 18-20 years old in competition - Gillard, M. (5th EHF Scientific Conference "Handball for Life", 21.-22.11.2019, Cologne, 2020)
The most talented young handball players start to move from youth to the teams of men clubs and then replenish the ranks of the national team, while others, having been injured, say "goodbye" to handball. The study analyzes a comparison of injuries of handball players of 18-20 years old, identify the main types of injuries of handball players of different ages and game positions in order to develop and apply effective means of injury prevention at the earlier stages of long-term training.